2022
DOI: 10.3390/ijms23020821
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Response in a Sepsis Mouse Model Reflects Transcriptional Response in Sepsis Patients

Abstract: Mortality due to sepsis remains unacceptably high, especially for septic shock patients. Murine models have been used to better understand pathophysiology mechanisms. However, the mouse model is still under debate. Herein we investigated the transcriptional response of mice injected with lipopolysaccharide (LPS) and compared it to either human cells stimulated in vitro with LPS or to the blood cells of septic patients. We identified a molecular signature composed of 2331 genes with an FDR median of 0%. This mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
(85 reference statements)
2
6
0
Order By: Relevance
“…As recently described, LPS administration in these settings results in the upregulation of the serum levels of TNFα and IL-6 [ 19 ]. The corresponding mRNA levels of TNF, IL-1b and IL-6 in the liver, spleen and lung tissues were also found to be increased ( Figure S2 ), as previously shown [ 20 ]. Normal saline alone was administered to littermate mice; the survival and health status of mice were monitored every 4 h during the light period.…”
Section: Resultssupporting
confidence: 85%
“…As recently described, LPS administration in these settings results in the upregulation of the serum levels of TNFα and IL-6 [ 19 ]. The corresponding mRNA levels of TNF, IL-1b and IL-6 in the liver, spleen and lung tissues were also found to be increased ( Figure S2 ), as previously shown [ 20 ]. Normal saline alone was administered to littermate mice; the survival and health status of mice were monitored every 4 h during the light period.…”
Section: Resultssupporting
confidence: 85%
“…Plk3 has been connected to inflammatory cell function as Plk3 mRNA and protein expression is enhanced in human macrophages as they transition from peripheral monocytes to attached macrophages 12 . Similarly, Plk3 mRNA expression is quickly elevated in LPS-treated mouse peritoneal cells 13 . These data suggest that Plk3 expression is enhanced during infection or the early stages of sepsis in both mouse and human.…”
Section: Discussionmentioning
confidence: 94%
“…Two studies of the effect of LPS stimulation in vivo in mice have recently also shown strong effects on both mRNA levels in inflammatory cytokines and chemokines and on protein levels in the serum of IL-6, TNF-α, IL-1β and IL-8 when using levels of LPS comparable or higher than what we use in vitro [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%